STRATEGI MAJELIS ULAMA INDONESIA (MUI) MANDAILING NATAL DALAM MENGEMBANGKAN EKONOMI ISLAM - Putri Citra Setiawati (EKSYA : Jurnal Ekonomi Syariah, 2024)
The Indonesian Ulema Council (MUI) of Mandailing Natal plays a crucial role in providing guidance and direction to the community regarding Islamic teachings. This study aims to explore MUI's contributions in maintaining social harmony and addressing issues related to Islamic economics in the region. The research employs a qualitative method with in-depth interviews conducted with MUI members and community leaders. The findings indicate that MUI actively issues fatwas using strategies such as providing religious education in both social and economic aspects and mediating conflicts. Several factors support MUI’s effectiveness, including support from the local government, public trust, and collaboration with other institutions. Thus, MUI in Mandailing Natal functions not only as a religious institution but also as a pillar of social and economic stability, reinforcing religious values within the community.